2006
DOI: 10.1007/s11284-006-0054-4
|View full text |Cite
|
Sign up to set email alerts
|

Configuration of small patch reefs and population abundance of a resident reef fish in a complex coral reef landscape

Abstract: Habitat use by the resident coral reef anemonefish, Amphiprion frenatus, was examined in the complex coral reef landscape of Shiraho Reef, Ishigaki Island, Okinawa, Japan, using an enlarged color aerial photograph processed using image analysis software as an accurate field map. The anemonefish inhabit assemblages of the host sea anemone, Entacmaea quadricolor (clonal type), which inhabit various patch reefs in the back reef moat. We located all patch reefs inhabited by the host in the map based on snorkel obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…A. frenatus is essentially omnivorous, although it feeds on algae, and it does not show strong territoriality (Allen 1975). It also forms larger colonies in larger reefs, which are usually taller three-dimensional reefs with large vertical walls, and larger reefs inhabited by A. frenatus provide refuge for other damselfishes (Hattori and Kobayashi 2007). Shibuno (unpublished data) also observed that A. frenatus was almost always found in sites where the species richness of other damselfishes is very high in shallow back reef habitats.…”
Section: Species-area Relationship On a Very Fine Scalementioning
confidence: 91%
“…A. frenatus is essentially omnivorous, although it feeds on algae, and it does not show strong territoriality (Allen 1975). It also forms larger colonies in larger reefs, which are usually taller three-dimensional reefs with large vertical walls, and larger reefs inhabited by A. frenatus provide refuge for other damselfishes (Hattori and Kobayashi 2007). Shibuno (unpublished data) also observed that A. frenatus was almost always found in sites where the species richness of other damselfishes is very high in shallow back reef habitats.…”
Section: Species-area Relationship On a Very Fine Scalementioning
confidence: 91%
“…The field study was conducted between September 2003 and 2006 in Shiraho Reef, Ishigaki Island (24°22¢N, 124°15¢E), Okinawa, Japan (Kobayashi and Hattori 2006;Hattori and Kobayashi 2007;Tamura et al 2007). We used a large-sized aerial photograph (92 · 92 cm 2 ), which was enlarged from the original negative of the aerial color photograph of Shiraho Reef (23 · 23 cm 2 , OKC-94-13, 1/10,000, 95 Ishigaki C15-34, Geographical Survey Institute, Ministry of Land, Infrastructure and Transport, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…However, those cannot cover seascape composition and the spatial distribution patterns of individuals, especially in low-density species. Hattori and Kobayashi (2007) developed a simple technique to incorporate the fine-scale seascape composition in a 3-ha field survey, including areas of habitat patches and habitat use by the giant sea anemone (Entacmaea quadricolor), which hosts anemonefish (Amphiprion frenatus), in shallow back reefs. In their study, they used an enlarged section of a high-resolution color aerial photograph (less than 0.1 m) to produce an accurate seascape map (equivalent to 1/2,500 scale or more).…”
Section: Introductionmentioning
confidence: 99%
“…Hattori and Shibuno (2010) investigated species richness and abundance of individuals of damselfishes among 84 small patch reefs and found that abundance of anemonefish Amphiprion frenatus was most positively correlated to damselfish species richness. In addition, Hattori and Kobayashi (2007) reported that total area of dark-colored patch reefs that were detected on aerial images reflects total number of A. frenatus, although they used analog type aerial photographs and did not distinguish tall patch reefs (>1.5 m in height) from the dark-colored patch reefs. The objective of the present study was to examine whether total area of tall patch reefs (>1.5 m in height) that are detectable on stereoscopic aerial images, as well as total area of dark-colored patch reefs that are detectable on ordinary aerial images, can be used for habitat quality assessment of the anemonefish.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of the present study was to examine whether total area of tall patch reefs (>1.5 m in height) that are detectable on stereoscopic aerial images, as well as total area of dark-colored patch reefs that are detectable on ordinary aerial images, can be used for habitat quality assessment of the anemonefish. Total area of dark-colored patch reefs can be compared with the results of Hattori and Kobayashi (2007). Underwater observations on patch reefs were also conducted to confirm relationships between anemonefish abundance and total area of patch reefs.…”
Section: Introductionmentioning
confidence: 99%